Investigation of Fruit Quality and Biochemical Traits of Rosehip (R. canina) Ecotypes in the Aegean Region of Türkiye - Halil Ibrahim Sagbas (Horticulturae, 2023)
Rosehip is a valuable fruit species in particular for rural populations. In this study, fruit quality parameters of 15 wild grown rosehip ecotypes naturally obtained from seeds in the Aegean Region of Türkiye were determined. The fruit weight, fruit firmness, fruit flesh ratio, fruit shape index, fruit skin color (chroma), soluble solid content, vitamin C, total phenolic, total carotenoid, total anthocyanin, total flavonoid and antioxidant capacity were investigated. The results showed great diversity among ecotypes. The fruit weight, fruit firmness, fruit flesh ratio, fruit shape index, fruit skin color (chroma) and soluble solid content were between 2.28 and 3.29 g, 4.70 and 7.12 N, 69.34 and 81.67%, 0.97 and 1.07, 53.04 and 60.71 and 18.87 and 21.28%, respectively. The total antioxidant capacity was found to be 15.78–28.17 mg AAE/g in a DPPH assay. The vitamin C content of rosehip fruits was measured as 507–621 mg/100 g. Among ecotypes, A-15 gave the biggest fruits, A-1 had the highest soluble solid content and A-13 had the highest vitamin C content. These results suggested that some ecotypes showed more potent bioactive properties than other ecotypes, mainly related to the variations in the antioxidant capacity and bioactive content between ecotypes. Overall, this study provides additional insight into investigating the genotype exhibition of multifunctional bioactive properties.